Relación de la aptitud aeróbica y muscular con niveles de actividad física en estudiantes universitarios - Gomez-Campos, Rossana (2025)
Introduction. Regular participation in physical activity (PA) programs is essential to maintain and improve physical and psychological health at all stages of life. Objective. To relate aerobic and muscular fitness to PA levels in young men and women from a university in Chile. Methods: A cross-sectional descriptive study was carried out, evaluating 186 university students (102 females and 84 males) aged 18 to 25 years.  Weight and height were evaluated. Body mass index (BMI) was calculated. Physical tests were evaluated: Navette test, manual grip strength [FPM (right and left hand)], abdominal test and arm flexion test. A PA questionnaire with 11 questions was applied. Results. There was a positive correlation between PA values and aerobic fitness indicators (meters run, absolute and relative VO2) (women: r= 0.19 to 0.22, men: r= 0.40 to 0.43) and muscle fitness indicators (right and left FPM, sit-ups, push-ups) (women: r= 0.17 to 0.26, men: r= 0.11 to 0.37). Conclusión. Higher PA levels are associated with better aerobic and muscular fitness in young university students, especially in men. Only those with high PA showed superior physical performance, suggesting the implementation of PA programs.